THE STUDY OF INTERLINGUAL AND INTRALINGUAL ERRORS OF STUDENTS’ DESCRIPTIVE WRITING AT ONE PRIVATE UNIVERSITY IN SINTANG - Wa Ode Ritna Yuniyr Ullah; Sijono Sijono (Journal of English Educational Study (JEES), 2018)
This study aims to investigate the errors that students made in writing descriptive text in a private university in Sintang and mainly focuses on interlingual and intralingual errors. This study used descriptive qualitative method and confirmed that the errors made by the students in the concerned private  university was dominated by the intralingual error which happened in more than half cases of errors made by the students or around 68.75%. In addition, interlingual error were also found in the students’ descriptive text, but its appearance was less than a half from all cases (i.e. 31.25%). From this findings, it was highly suggested that students be exposed more seriously to the target language.Keywords: Interlingal error; Intralingual error; Descriptive Writing